CORPORATE GOVERNANCE MODERATING THE EFFECTS BOOK TAX DIFFERENCES TO EARNING PERSISTENCE - Utari, Luh Ayu Pujiastini; Mertha, I Made (E-Jurnal Akuntansi, 2016)
The purpose of this study is to proof the empirical of the influence book tax differences on the earnings persistence moderated by corporate governance in all of the companies that have been registered in BEI on period 2011-2014. Method of sample selection that used in this study is purposive sampling, decent samples to be observed are 42 companies. The data analyzed used double linier regretion and MRA. The result of this study indicated 1) Companies with LPBTD and LNBTD has no influence on earnings persistence, 2) The corporate governance debilitated the influence of LPBTD on the earnings persistence significanly meanwhile the corporate governance did not debilitate the influence of LNBTD on the earnings persistence.
Keywords: earnings persistence, book tax differences, corporate governance